Upaya Peningkatan Hasil Belajar Siswa Mata Pelajaran Matematika Materi Pecahan Sederhana Dengan Metode Demonstrasi Dan Diskusi Pada Kelas III Semester Iidi Sekolah Dasar Negeri Kotakan Tahun Pelajaran 2019/2020 - Sugrati L., Hevlin (Yayasan Darussalam Bengkulu, 2021)
The background of this research is that students find it very difficult with geomery and measurement material in mathematics, because of that many students get low scores. This condition affects student achievement which is still low. Therefore, it is necessary to conduct research to improve the mindset of students in learning and improve student achievement in grade 3 SDN Kotakan Kec. Karanganyar, Demak Regency. This type of research conducted in this research is classroom action research. The focus of the research is efforts to improve students' abilities in completing assignments, namely math problems, geometry and measurement material. In Class 3 Students SD N Kotakan, Karanganyar District, Demak Regency. Data collection was carried out by conducting observations, tests, interviews, field notes, documentation. The data analysis used is qualitative data which is analyzed by collaborators. The results showed: (1) the implementation stages of using the experimental method can be carried out in accordance with the theory used. (2) when learning the teacher is more creative, so that students are more enthusiastic and feel happy. This can be seen in the increasing class average score. In the pre-test the class average value of 64, while the class average value at the end of the action cycle I was 66, the class average at the end of the action cycle II was 72. Then in cycle II the learning outcomes were said to be complete because the average already above KKM 70.